Comprehensive Transcriptome and Metabolic Profiling of Petal Color Development in Lycoris sprengeri - Yang, Feng; Li, Chao-han; Das, Debatosh; Zheng, Yu-hong; Song, Tao; Wang, Lan-xiang; Chen, Mo-Xian; Li, Qing-zhu; Zhang, Jianhua (Frontiers in Plant Science, 2021)
Lycoris sprengeri (L. sprengeri) is an important ornamental bulbous plant and numerous varieties are widely planted with different color forms. Multiple color types of petals in L. sprengeri provides us with possibilities to delineate the complicated metabolic networks underlying biochemical traits behind color formation in this plant species, especially petal color. In this study, we sequenced and annotated a reference transcriptome of pink and white petals of L. sprengeri and analyzed the metabolic role of anthocyanin biosynthesis in regulating color pigment metabolism. Briefly, the white and pink petal samples were sequenced with Illumina platform, to obtain reads that could be assembled into 100,778 unique sequences. Sequences expressed differentially between white vs pink petals were further annotated with GO, COG, KEGG and eggNOG terms. Gene expression analyses revealed repression of anthocyanin and steroid biosynthesis enzymes and R2R3 MYB transcription factor (TF) genes in the white petals compared to the pink petals. Furthermore, targeted metabolic profiling of anthocyanins revealed that color-related delphinidin (Del) and cyanidin (Cy) pigments are lower in white petals which correlates well with the reduced gene expression levels of anthocyanin biosynthesis genes. Taken together, it is hypothesized that anthocyanin biosynthesis, steroid biosynthesis and R2R3 MYB TF may play vital regulatory roles in petal color development in L. sprengeri. This work provides a valuable genomic resource for flower breeding and metabolic engineering in horticulture and markers for studying flower trait evolution of L. sprengeri.